Seed compositional and disease resistance differences among gene pools in cultivated common bean - Islam, F.M.A.; Basford, KE; Jara, Carlos E.; Redden, R.J.; Beebe, Stephen E. (Springer, 2002)
It is widely accepted that two major gene pools exist in cultivatedcommon bean, one Middle American and one Andean. Recently another gene pool,designated as North Andean and a fourth group (not considered to be adistinct gene pool) have been reported by the senior author and hiscolleagues. Many of the agronomic and seed compositional attributes of the twomajor gene pools are well known, but the seed compositional value and diseaseresistance of the North Andean gene pool has not yet been characterized. Torectify this situation, the seed compositional characters, percentage of proteinconcentrations (phaseolin, lectin and ?-amylaseinhibitor), the nutrient elements (calcium, phosphorus, iron andzinc) and the disease and pest attributes (angular leaf spot,anthracnose, common bacterial blight and empoasca damage) were considered.The Middle American gene pool gave higher lectin, calcium, phosphorus, sulfurand zinc than the Andean gene pool but lower phaseolin and iron. The NorthAndean gene pool is more like the Andean gene pool for phaseolin, resistance toangular leaf spot and anthracnose from Andean pathogen isolates, but more likethe Middle American gene pool for lectin, zinc, sulfur and resistance toanthracnose from Middle American pathogen isolates. On the other hand, it hadthe highest iron concentration and was more resistant to common bacterialblight. These results indicate the potential value of this gene pool in a commonbean breeding program.